Strategi Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) Untuk Meningkatkan Perekonomian Masyarakat Dihuntap Pombewe Kabupaten Sigi - Fani Fani; Elimawaty Rombe; Syamsul Bachri; Mohammad Riswandi Palawa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Pombewe Huntap is a relocation place for residents affected by disasters in Sigi Regency, Central Sulawesi, especially for residents from Oloboju, Jono Oge, Loru, and Pombewe Villages. The majority of Pombewe Huntap residents work in the agriculture, livestock and Micro, Small and Medium Enterprises (MSMEs) sectors. MSMEs have a vital role in national economic growth, but their development in Pombewe Huntap still faces obstacles. The purpose of this research is to find the best way to develop MSMEs to improve the economy of the Pombewe Huntap community in Sigi Regency. The results showed that Pombewe Huntap MSMEs face major problems related to capital, marketing, and production. This study suggests the village government to improve existing programs to support MSMEs, including training, financial assistance, and provision of equipment, as well as consistent evaluation of results.